Food handling in the domestic environment: an online questionnaire study with respondents from 24 of 26 Brazilian states - Sampaio, Aryele Nunes da Cruz Encide; Soares, Vanessa Mendonça; Tadielo, Leonardo Ereno; Santos, Emanoelli Aparecida Rodrigues dos; Cerqueira-Cézar, Camila Koutsodontis; Danelon, Giovanni Costa; Bersot, Luciano dos Santos; Pereira, Juliano Gonçalves (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Using an online questionnaire, this study evaluated the profile of a Brazilian population’s food handling practices in the home environment. The questionnaire, containing questions about domestic behavior in terms of hygiene and food handling, was built and available through social media sites. Information about the participants’ profiles, their food pre-preparation, food preparation, and food post-preparation practices, and the occurrence of foodborne diseases (FBDs) was included in the questionnaire. A total of 701 responses were obtained. The interviewees included 78.31% female participants and 21.68% male participants, with an average age of 31.2 years. Nearly all (94.3%) had a complete or incomplete higher education. In the pre preparation stage, the participants evaluated the shelf life (97.28%) and storage temperature (44.79%) of the products while purchasing them. Regarding food handling practices, only a few participants washed the food packages before storing them (31.95%) or removed hand jewelry or other adornments when washing food (61.48%). Most participants washed their hands (91.58%) and washed vegetables (99.28%). But a group of interviewees reported washing raw meat (27.81%) before preparing it. Cutting surfaces such as plastic (50.36%) and glass (49.36%) tops were the most prevalent in the study. Most respondents did not know how long they had been using their cutting boards (67.62%) and mentioned using the same surface to handle both raw and ready-to-eat products (84.17%). As for the preparation, most interviewees declared they did not check the food temperature during preparation (86.31%), ignoring the ideal cooking temperature (88.26%). Regarding the occurrence of FBDs, 79.17% of the interviewees reported having suspicious clinical signs associated with contaminated foods and 65.59% did not seek medical help. Thus, the participants demonstrated ignorance about adequate practices for food safety in the home environment, highlighting the need to conduct health education programs within the Brazilian population.